PIRLS RESEARCH PROCEDURE AND STANDARDIZATION AND RESEARCH TOOLS (American Journal of Pedagogical and Educational Research, 2023)
The article describes the requirements, advantages of the international assessment program PIRLS, its procedure and research tools.